The effects of leadership for self-worth, inclusion, trust, and psychological safety on medical error reporting. Issue 2 (April 2023) - Brimhall, Kim C.; Tsai, Chou-Yu; Eckardt, Rory; Dionne, Shelley; Yang, Biying; Sharp, Adam
Abstract : Background: Although trust and psychological safety (PS) are critical for improving patient safety and medical error reporting, little is known about how they work together and how health care systems promote PS. Purpose: This study examined how leadership for self-worth, inclusion, and trust may work together to foster PS and how this influences medical error reporting. Approach: Data were collected in 2019 from 373 employees (24% response rate) in 85 hospital departments (54% response rate) in a nonprofit health care system in the eastern United States. Constructs were operationalized at the department level. Results: Negative binomial path model results found several direct effects. Leadership for self-worth was positively associated with inclusion, inclusion was positively associated with trust and PS, trust was positively associated with reported medical errors, and PS was negatively associated with reported medical errors. Indirect effects uncovered leadership for self-worth was positively associated with PS by enhancing inclusion. In addition, leadership for self-worth increased inclusion, which increased trust and ultimately encouraged PS. Leadership for self-worth was associated with fewer reported medical errors through increasing inclusion, trust, and PS. Practical Implications: Trust encourages the formal reporting of medical errors whereas PS encourages learning from mistakes and improving care to reduce future errors (and consequently the number of reported errors). Leaders who understand employees' unique needs, express confidence in employees' abilities, and encourage employees to share their ideas, create inclusive and trusting work environments that encourage PS and ultimately help reduce reported medical errors.